2022
DOI: 10.3389/fpsyt.2022.829944
|View full text |Cite
|
Sign up to set email alerts
|

A “Good” Smoke? The Off-Label Use of Cannabidiol to Reduce Cannabis Use

Abstract: BackgroundAlthough cannabis use is common in France, it is still criminalized. Cannabidiol (CBD) products, including CBD-rich cannabis, are legally available. Although previous results suggested that CBD may have benefits for people with cannabis use disorder, there is a lack of data on cannabis users who use CBD to reduce their cannabis consumption. We aimed to identify (i) correlates of this motive, and (ii) factors associated with successful attempts to reduce cannabis use.MethodsA cross-sectional online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…Our cluster analysis confirmed the relationship between cannabis and CBD use, suggesting that cannabis cousers constitute a distinct category of CBD users [26,30,31]. Given results from human studies and observational data, we can hypothesise that some people use CBD in an attempt to reduce their cannabis consumption [31,32]. We also found that poor self-reported general health status was associated with a higher likelihood of using CBD, and that health characteristics differ between clusters, suggesting CBD is used for therapeutic reasons [17].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our cluster analysis confirmed the relationship between cannabis and CBD use, suggesting that cannabis cousers constitute a distinct category of CBD users [26,30,31]. Given results from human studies and observational data, we can hypothesise that some people use CBD in an attempt to reduce their cannabis consumption [31,32]. We also found that poor self-reported general health status was associated with a higher likelihood of using CBD, and that health characteristics differ between clusters, suggesting CBD is used for therapeutic reasons [17].…”
Section: Discussionsupporting
confidence: 74%
“…Clusters differed in terms of age, gender, city size, tobacco and cannabis use, health characteristics and their view on the alternative medicines statement (Table 3). Our cluster analysis confirmed the relationship between cannabis and CBD use, suggesting that cannabis cousers constitute a distinct category of CBD users [26,30,31]. Given results from human studies and observational data, we can hypothesise that some people use CBD in an attempt to reduce their cannabis consumption [31,32].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, it does reflect findings that besides being more common among tobacco users, CBD use is also more common among cannabis users [47], including users in France [31]. This would suggest that it is smoked in the form of CBD‐rich, low‐THC cannabis flowers, particularly if used as a substitute and/or a means for reducing cannabis use [47, 48].…”
Section: Discussionmentioning
confidence: 97%
“…Fortin and colleagues [ 46 ] recently reported findings from an online anonymous survey of French residents who reported having used CBD within the past month. Respondents reported using CBD primarily to reduce their use of (illicit) cannabis.…”
Section: Introductionmentioning
confidence: 99%